Penerapan Model Pembelajaran Quantum Teaching dalam Meningkatkan Motivasi Belajar Mahasiswa PGSD Universitas Muhammadiyah Sidoarjo: Application of Quantum Teaching Learning Model in Improving Learning Motivation of PGSD Students at Muhammadiyah University of Sidoarjo - Rezania, Vanda (Pedagogia : Jurnal Pendidikan, 2018)
This study aims to determine the increased learning motivation of PGSD students of Muhammadiyah University of Sidoarjo after the implementation of the Quantum Teaching learning model. The research method used is Classroom Action Research (CAR) which consists of two cycles. Cycle (I) consists of the activities of Planning, Implementation, Observation, and Reflection conducted during two meetings. Likewise with cycle (II), which is done during two meetings. Data collection techniques that are applied are observation techniques, filling out motivation learning questionnaires, interviews, and documentation. Data processing used is descriptive percentage. The results showed that there was an increase in the average score of the learning motivation of PGSD students of Muhammadiyah Sidoarjo University A1 Semester 1 class from a score of 67.9% (cycle I) to 80.1% (cycle II) through the application of the Quantum Teaching learning model. The conclusion of this study is that there is an increase in learning motivation of PGSD students at Muhamamdiyah Sidoarjo University after the implementation of the Quantum Teaching learning model.